2010
DOI: 10.1021/jf903857m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan on Hepatic Drug-Metabolizing Enzymes and Oxidative Stress in Rats Fed Low- and High-Fat Diets

Abstract: Chitosan is sold worldwide as a lipid-lowering functional food and may be taken with certain medications. To investigate the effect of chitosan on drug-metabolizing enzymes and oxidative stress in the liver, male Wistar rats were fed a low- or high-fat diet with cellulose or chitosan for 4 weeks. A significant decrease in cytochrome P450 (CYP) 3A-catalyzed testosterone 6beta-hydroxylation in liver microsomes was observed in rats fed the chitosan with low- and high-fat diets. The expression of CYP 3A1 and 3A2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Chitosan is a linear polysaccharide containing various proportions of GlcN [ 3 ]. It has applications in nutritional [ 4 ], agricultural [ 5 ], and medical areas [ 6 , 7 , 8 ]. However, its poor solubility in aqueous solutions and its high viscosity are problematic for those applications.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a linear polysaccharide containing various proportions of GlcN [ 3 ]. It has applications in nutritional [ 4 ], agricultural [ 5 ], and medical areas [ 6 , 7 , 8 ]. However, its poor solubility in aqueous solutions and its high viscosity are problematic for those applications.…”
Section: Introductionmentioning
confidence: 99%
“…The Western blot analysis was performed as described previously [33]. The liver homogenates of each group with equal amounts of protein were separated by SDS-PAGE and transferred to polyvinylidene difluoride membranes.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Currently, chitosan is widely used as pharmaceutical foods because of its biocompatibility, nontoxicity and adsorption (Dass and Choong 2008;Bonferoni et al 2009). Previous studies have also shown that chitosan has a lipid-lowering effect resulting from a decrease in the metabolism of intestinal bile acids (Ylitalo et al 2002;Yao et al 2010). Additionally, chitosan has been reported to have immunomodulating (Lim et al 1997) and anticancer effects, including the inhibition of cancer cell proliferation (Tokoro et al 1988), angiogenesis (Murata et al 1991) and metastasis (Murata et al 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have also shown that chitosan has a lipid‐lowering effect resulting from a decrease in the metabolism of intestinal bile acids (Ylitalo et al . 2002; Yao et al . 2010).…”
Section: Introductionmentioning
confidence: 99%